(untitled) (Bangladesh Journal of Public Administration, 2021)
Dunning (2006) asserted that international business research focused heavily on the physical assets of organizations and nations, thus neglecting the human environment of organizations and nations.Research has shown “the most important driver for economic advancement is knowledge” and is drawn from the human environment (Zhu et al., 2011, p. 312). The human environment is defined as the “human assets (i.e. creativity leading to innovation; experience, skills and knowledge of employees) and the skills and abilities those assets possess within a given location” (Zhu et al., 2011, p. 312).Thus, how an organization, including government, manages its human resources (HR), drawn from the human environment in which it operates, will significantly impact success or failure (Barney, 2001; Kong & Thomson, 2009).We contend that although there has been a great deal of research on human resource management (HRM) as a competitive advantage for firms, there has been little work done on the analysis of HRM practices in government and its influence on a nation’s competitive advantage. In a qualitative study of a developing nation in the Caribbean we interviewed 12 senior level employees. Our analysis revealed that little attention was paid to HRM, which resulted in the ineffectiveness of the application of government policies. The data revealed that issues started with the recruitment and selection processes.This paper focuses on the recruitment and selection processes utilized by government agencies that cause institutional voids which lead to the failure to utilize public service employees as a source of competitive advantage.